An analysis on work happiness among university staff in a Malaysian context - Alby, Jeffrey Lawrence D'Silva; M. Yassin, Sulaiman; Abu Samah, Asnarulkhadi; Omar, Siti Zobidah; Abdul Wahat, Nor Wahiza; Dahalan, Dzulhilmi; Mohamed Shaffril, Hayrol Azril; Kamaruddin, Nuraini (Serials Publications, 2017)
Much had been mentioned about workplace happiness as it is poised to enhance productivity and organizational development. It was identified that little empirical evidence is available on the level of happiness among university staff. Thus, this study investigates the happiness index of a public university in Malaysia. A total of 856 university staff both academic and non-academic participated in this study. Previous literature and a nominal group technique method were used to develop the instrument of the study. Overall, the findings showed that the happiness index stood at 70.19 indicating generally the staff are happy working in the university. The study suggests that to further enhance happiness among university staff emphasis should be placed to improve on communications, infrastructure, and human resource management.